The Influence of Online Service Quality towards Customer Satisfaction and Repurchase Intention in Chinese Fresh E-commerce - Xiaomei, Han (UNIMAS, 2025)
China’s fresh e-commerce has expanded rapidly, yet service-quality volatility, rising complaints, and unstable repurchase behavior persist. The category’s perishability, time sensitivity, cold-chain dependence, and high-frequency, low-ticket transactions make customer experience especially sensitive to fulfillment, logistics, customer service, and price perceptions. Against this backdrop, the study focuses on the mechanism linking service quality, satisfaction, and repurchase intention. Existing research on fresh e-commerce provides incomplete empirical evidence on the service quality–satisfaction–repurchase mechanism. First, it relies heavily on cross-sectional questionnaires and lacks large-scale observations rooted in real purchasing and review contexts, limiting visibility into negative experiences and exception handling. Second, samples often come from a single platform or business model, overlooking heterogeneity across front-warehouse systems, store-warehouse integration, community group-buying, and comprehensive e-commerce, which constrains external validity. Third, prior work insufficiently distinguishes which service elements directly drive repurchase versus those that act primarily through satisfaction, and systematic mediation testing remains scarce. Therefore, there is a need to build and test an integrated model on multi-platform, real review data to clarify key paths and effect sizes linking service quality to satisfaction and repurchase. This study tests the effects of online service-quality dimensions on customer satisfaction and repurchase intention and evaluates the mediating role of satisfaction. Specifically: (i) examine the effect of service quality on satisfaction; (ii) test the direct effect of service quality on repurchase intention; (iii) assess the effect of satisfaction on repurchase intention; and (iv) evaluate the mediating role of satisfaction in the relationship between service quality and repurchase intention. Using 56,765 user reviews from JD Fresh, Dingdong Maicai, Yonghui Delivery, and Taocaicai, the study applies BERTopic to extract service topics and elements. Subsequently, Baidu NLP’s sentiment classifier assigns polarity (positive/neutral/negative) score to review texts mapped to each service-quality dimension, and the resulting scores are aggregated as measurement indicators. Direct and indirect effects are estimated via structural equation modeling (SEM), with mediation evaluated through bootstrap resampling. Logistics service quality, customer service, and economic efficiency exhibit significant positive direct effects on repurchase intention. Fulfillment and ease of use significantly improve satisfaction but do not directly drive repurchase. Satisfaction both positively influences repurchase intention and plays a pivotal mediating role between service quality and repurchase. Fresh e-commerce platforms should strengthen cold-chain operations, ensure on-time delivery, improve after-sales response, align pricing and membership benefits, and reduce errors in fulfillment and design. At the policy level, higher standards and review-based monitoring can promote healthier competition.